Sugar Palm Fibre-Reinforced Polymer Composites: Influence of Chemical Treatments on Its Mechanical Properties - Asyraf M.R.M.; Syamsir A.; Supian A.B.M.; Usman F.; Ilyas R.A.; Nurazzi N.M.; Norrrahim M.N.F.; Razman M.R.; Zakaria S.Z.S.; Sharma S.; Itam Z.; Rashid M.Z.A. (MDPI, 2023)
Fibers; Plastic products; Reinforcement; Biomass wastes; Chemical treatments; Fiber reinforced polymer composites; Global community; Globalisation; Lignocellulosic fibres; Natural fiber composites; Sugar palm; Sugar palm fiber; Thermosetting and thermoplastic; Fiber reinforced plastics